Blue Economy and Smart Sea Transport Systems Maritime Security - Gujar, Girish Chandrakant; Ng, Adolf K. Y. (Cham : Springer International Publishing : Imprint: Springer, 2023)
Focusing on maritime security, this book discusses Blue Economy and Smart sea transport systems in the context of the Indian Ocean rim countries and the multifaceted challenges that they are likely to face while attempting to develop such systems. It introduces Blue Economy as a concept with an emphasis on lower costs, reduced waste, greater efficiency, and value addition in all services associated with the near and deep oceans, with the establishment of Smart sea transport systems as the adaptive response in a global trade system. It highlights the roles of maritime security in politics, economics, and environmental management issues that constitute the challenges of achieving such goals. In this regard, the authors approach the issues from the institutional perspective to examine ways in which relevant transport and supply chain stakeholders can collaborate to build secure, resilient global systems of maritime trade. This book will be of interest to anyone interested in marine policy and global supply chains, especially in maritime security, its impacts and risks on transport and supply chain infrastructures, and the related socioeconomic activities likely to be affected. Readers will gain insight into the effective ways to adapt to such risks and how to benefit from the generated opportunities on transport, supply chains, and the global economy. Also, it is an ideal companion to policymakers and practitioners who are eager to learn about the dynamics between maritime security and Blue Economy which, in turn, enhances the quality of strategic planning, policies, and practices in addressing these issues. Finally, it inspires researchers and postgraduate students to conduct innovative research on this topic.
Chapter1. Introduction -- Chapter2. Maritime Security - Call of the Seas -- Chapter3. Jurisdictional Issues of the Seas -- Chapter4. Coastal and Port Security -- Chapter5. Blue Economy and Smart Sea Transport Systems -- Chapter6. Towards a Sustainable Global Growth -- Chapter7. Maritime Clusters -- Chapter8. Public Private Partnerships and Port- Land Interface Projects -- Chapter9. The Pandemic, the Blue Economy and the Way Forward.
Keywords: Economic geography; Economics; Security, International; Production management; Economic Geography; Economics; International Security Studies; Operations Management